EVALUASI LAYANAN INFORMASI MITIGASI BENCANA MELALUI WEBSITE PANTAU BANJIR DI KOTA SEMARANG - Charisa Mellasyafa Agustien; Amni Zarkasyi Rahman; Retno Sunu Astuti (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2023)
The flood monitoring information service website was created to as government efforts to detect dink flood disasters in Semarang City, However, the flood disaster still continues in Semarang, indicating that the webiste has not been utilized to the maximum extent. So the purpose of this study is to evaluate the website information service monitoring the flood in Semarang City. This research uses the theory of the effectiveness of e-government online services by Xuetao Guo and Jielu, which consists of system quality, information quality, web presence quality and user satiety. This type of research uses a quantitative approach with a descriptive type of research. The population of this study is all users of the flood monitoring website with a sample of 100 respondents using purposive sampling techniques. Evaluation results based on research show system quality score 84.01% with excellent category. information quality 84.56% with excellent category, web presentation quality score 87.94% with excellent category, user satisfaction 78.82% with good category, and web presentation quality score 87.94% with excellent category. However, there are still gaps (gap) in all dimensions, items that require major improvements are the response speed and ease of CCTV features, the completeness of flood disaster detection information, the overall quality of the system satisfies the user, and the overall quality of information satisfies the user.